Penguatan Tata Kelola Kebijakan Moderasi Beragama: Menjawab Tantangan Implementasi Struktural, Partisipatif, dan Solutif - Zakiah (JURNAL ILMIAH GEMA PERENCANA, 2025)
This article aims to analyze the effectiveness of the implementation of the Kampung Moderasi Beragama (KMB) Program initiated by the Indonesian Ministry of Religious Affairs to mainstream the values of tolerance, balance, and harmony in religious life. The study employs a descriptive-qualitative approach supported by quantitative data and field interviews in North Maluku Province, using the theoretical framework of policy implementation by Mazmanian and Sabatier, as well as Arnstein’s Ladder of Citizen Participation. The findings reveal several critical challenges, including low public understanding of religious moderation, weak stakeholder coordination, limited community involvement, and insufficient budgetary support. Furthermore, the existence of dual programs—KMB managed by the Directorate General of Islamic Community Guidance and the Desa Sadar Kerukunan (DSK) run by the Center for Religious Harmony—creates overlapping authorities and confusion among local implementers. This article recommends merging both programs into a single, inclusive initiative under the coordination of the Center for Religious Harmony (PKUB), involving multi-faith religious counselors at the grassroots level. Reforming the monitoring and evaluation system, expanding public literacy on religious moderation, and shifting to a collaborative approach are crucial prerequisites for enhancing the effectiveness, efficiency, and sustainability of the program.